3.129. Rozwiąż równanie: a) (x ^ 2 – 4) ^ 2 = 9(x ^ 2 – 4) c) (x ^ 2 + 2x) ^ 2 + 9 = 6x ^ 2 + 12x e) (x ^ 2 – x) ^ 2 = 20x ^ 2 – 20x b) (x ^ 2 + 1) ^ 2 = 3 + x ^ 2 – 5x ^ 4 d) (x ^ 2 – x + 3)(x ^ 2 + 2x) = x(6 + x ^ 2) f) 3(x ^ 4 + 3) = (x ^ 2 – 1) ^ 2 + 12x ^ 2 b) (x ^ 2 + 6)(7 – x ^ 2) – 36 = x ^ 4 + 12x ^ 2 d) (x ^ 2 – 1) ^ 2 – 4(x ^ 2 – 1) + 4 = 0 f) (x ^ 2 – 1) ^ 2 – (9x ^ 2 – 4) = 5 – 7x ^ 2 . b) (x ^ 2 + 3) ^ 2 – 5(x ^ 2 + 3) + 4 = 0 d) (x ^ 2 – 8x) ^ 2 + 5 = 2(x ^ 2 – 8x) f) (x ^ 2 + 3x – 1) ^ 2 + 7(x ^ 2 + 3x – 1) = – 12 Nierówności kwadratowe

 3.129. Rozwiąż równanie: a) (x ^ 2 – 4) ^ 2 = 9(x ^ 2 – 4) c) (x ^ 2 + 2x) ^ 2 + 9 = 6x ^ 2 + 12x e) (x ^ 2 – x) ^ 2 = 20x ^ 2 – 20x b) (x ^ 2 + 1) ^ 2 = 3 + x ^ 2 – 5x ^ 4 d) (x ^ 2 – x + 3)(x ^ 2 + 2x) = x(6 + x ^ 2) f) 3(x ^ 4 + 3) = (x ^ 2 – 1) ^ 2 + 12x ^ 2 b) (x ^ 2 + 6)(7 – x ^ 2) – 36 = x ^ 4 + 12x ^ 2 d) (x ^ 2 – 1) ^ 2 – 4(x ^ 2 – 1) + 4 = 0 f) (x ^ 2 – 1) ^ 2 – (9x ^ 2 – 4) = 5 – 7x ^ 2 . b) (x ^ 2 + 3) ^ 2 – 5(x ^ 2 + 3) + 4 = 0 d) (x ^ 2 – 8x) ^ 2 + 5 = 2(x ^ 2 – 8x) f) (x ^ 2 + 3x – 1) ^ 2 + 7(x ^ 2 + 3x – 1) = – 12 Nierówności kwadratowe